2006
DOI: 10.1029/2005jf000436
|View full text |Cite
|
Sign up to set email alerts
|

Updated estimates of glacier volume changes in the western Chugach Mountains, Alaska, and a comparison of regional extrapolation methods

Abstract: [1] We used airborne altimetry measurements to determine the volume changes of 23 glaciers in the western Chugach Mountains, Alaska, United States, between 1950/1957. Average net balance rates ranged between À3.1 to 0.16 m yr À1 for the tidewater and À1.5 to À0.02 m yr À1 for the nontidewater glaciers. We tested several methods for extrapolating these measurements to all the glaciers of the western Chugach Mountains using a process similar to cross validation. Predictions of individual glacier changes appear t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
122
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(130 citation statements)
references
References 46 publications
(69 reference statements)
7
122
1
Order By: Relevance
“…This concept is similar to extrapolating the mean of observed centerline surface elevation changes in altitude bands to unmeasured glaciers as proposed by Arendt et al (2006). Here, 100-yr mean mass balance of the data sets presented by Huss et al (2010a,b) is averaged in 100 m elevation bands in a first step.…”
Section: Glacier Hypsometrymentioning
confidence: 99%
See 2 more Smart Citations
“…This concept is similar to extrapolating the mean of observed centerline surface elevation changes in altitude bands to unmeasured glaciers as proposed by Arendt et al (2006). Here, 100-yr mean mass balance of the data sets presented by Huss et al (2010a,b) is averaged in 100 m elevation bands in a first step.…”
Section: Glacier Hypsometrymentioning
confidence: 99%
“…Extrapolation of single-glacier mass balance series to several thousand glaciers within a mountain range is not trivial and involves considerable uncertainties (e.g. Arendt et al, 2006). Differences in mass balance between neighbouring glaciers are more importantly controlled by glacier geometry than by regional climate variability; mass balance response to similar changes in forcing can differ by up to a factor of four (Kuhn et al, 1985;Abermann et al, 2011b;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The well documented pattern of thickness change along a longitudinal profile of a land terminating glacier is greatest thinning at the terminus, and at some distance above the terminus, usually in the accumulation zone, the glacier thins significantly less even during retreat (Paterson, 1981;Schwitter and Raymond, 1993). Arendt et al (2006) observed from repeat longitudinal profiles of glaciers in Alaska near zero changes at higher elevations, decreasing to a maximum rate of thinning at the elevation of the terminus. Johannesson et al (1989) and Schwitter and Raymond (1993) described a profile shape parameter f , this factor is a measure of the degree to which thickness change, h, is distributed along the length of a glacier.…”
Section: Equilibrium Responsementioning
confidence: 99%
“…The University of Alaska Fairbanks (UAF) Laser Altimetry Program has flown repeat centerline surface elevation profiles on over 200 glaciers across Alaska and adjoining Canada since 1993 Arendt et al, 2002Arendt et al, , 2006. Centerline profiles of the BGS were flown in June 1995and 2000, in August 2000, 2007, in September 2008and in August 2009 (Koenig et al, 2010).…”
Section: Airborne Altimetrymentioning
confidence: 99%